Padronização interna em espectrometria de absorção atômica - Fernandes, Kelly G. [UNESP]; Moraes, Mercedes de [UNESP]; Gomes Neto, José Anchieta [UNESP]; Nóbrega, Joaquim A.; Oliveira, Pedro V. (Sociedade Brasileira de Química, 2003)
This paper describes a review on internal standardization in atomic absorption spectrometry with emphasis to the systematic and random errors in atomic absorption spectrometry and applications of internal standardization in flame atomic absorption spectrometry and electrothermal atomic absorption spectrometry. The rules for selecting an element as internal standard, limitations of the method, and some comments about the application of internal standardization in atomic absorption spectrometry and the future of this compensation strategy are critically discussed.
Internal standardization in atomic absorption spectrometry
Keywords: internal standardization; atomic absorption spectrometry